Moringa Leaf Powder: A Natural Superfood with Nutritional Potential - Shweta Suryavanshi; Suryawanshi O.P. (Emerging Trends in Metabolites, 2025)
Malnutrition can be described by excesses, imbalances, or shortages in an individual’s energy and nutritional intake, according to the World Health Organization (WHO). The plant Moringa oleifera, which is indigenous to India, thrives in tropical and subtropical regions all over the world. The nutritional properties of Moringa are high and it is rich in calcium. The nutritional value of fresh moringa leaf is ranged as protein 6.9 g, ash 1.5–2.5%, crude fiber 1.75 g, carbohydrate 2.93 g, fat 1.5–2%, energy (kcal) 110–140l/100 g and calcium 390–420 mg, iron 6–8 mg, magnesium 38–42 mg, potassium 350–400 mg and zinc 0.60–0.80 mg and vitamin E – 113 mg, vitamin B1 – 2.64 mg, vitamin B2 – 20.5 mg, vitamin B3 – 8.2 mg, and vitamin C – 17.3 mg. After drying moringa leaves at 60℃ in a hot air oven for 5.25 hours, the nutritional properties of moringa leaves were increased. The nutritional value of moringa leaf powder ranged as protein 23.12 g, ash 7.8 g, crude fiber 11.43 g, carbohydrate 46.4 g, fat 5.25 g, moisture content of 6% per 100 g, and calcium 2300 mg, Therefore, the people who are suffering from malnutrition can consume this jaggery cubes including lactating women.
Keywords: Malnutrition; Moringa Leaf; WHO; carbohydrate; protein